2005
DOI: 10.1080/13600810500137764
|View full text |Cite
|
Sign up to set email alerts
|

China's Competitive Threat to Latin America: An Analysis for 1990–2002

Abstract: This paper explores China's competitive threat to Lat in America in trade in manufactures. The direct threat in exports to third country markets appears small: LAC's trade structure is largely complementary to that of China. In bilateral trade, several LAC countries are increasing primary and resource-based exports to China. However, the pattern of trade, with LAC specializing increasingly in resource-based products and China in manufactures, seems worrying. Given cumulative capability building, China's succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 8 publications
6
75
0
8
Order By: Relevance
“…They have used various methods, including inspection of trade data (e.g. Lall et al 2005;Mesquita Moreira, 2007;Kaplinsky and Morris, 2008), revealed comparative advantage calculations (Lederman et al, 2008), gravity models (e.g. Greenaway et al, 2008;Hanson and Robertson, 2010) and computable general equilibrium (CGE) models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They have used various methods, including inspection of trade data (e.g. Lall et al 2005;Mesquita Moreira, 2007;Kaplinsky and Morris, 2008), revealed comparative advantage calculations (Lederman et al, 2008), gravity models (e.g. Greenaway et al, 2008;Hanson and Robertson, 2010) and computable general equilibrium (CGE) models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the contributions in these volumes reflect, to varying degrees, the authors' concerns about such a model -that is, about 'a general trend for the region to become more specialized in production of primary products and resource based manufactures, while China specializes in manufactured goods which are becoming more technologically sophisticated over time' (Jenkins in Jenkins and Dussel Peters, 59). The argument is perhaps most clearly made in the various excellent contributions to the Jenkins and Dussel Peters volume and by Gallagher and Porzecanski, and indeed is commonly heard in the wider literature (see Lall and Weiss 2005;Mesquita Moreira 2007;Kaplinsky and Morris 2008;Phillips 2009Phillips , 2010. The concern relates to what is surely a 'backward' movement to a global positioning based on the export of raw materials, with all of its consequences for growth, processes of economic upgrading, and indeed social development.…”
Section: How Does the Global Expansion Of China Affect Economic Develmentioning
confidence: 93%
“…Nowadays, China is the largest trading partner of Brazil and the second largest of Argentina, Uruguay, and Paraguay. China's trade expansion in Latin America was initially depicted as an opportunity for most of Latin American countries, as their export structures were largely complementary (Lall, 2005;Blázquez-Lidoy et al, 2007;Qureshi & Wan, 2008;Lederman, 2009) and China's demand improved the trade terms of commodity exporting countries. Nonetheless, this optimistic tone faded while concerns grew given China's manufacturing competitiveness, especially in economies belonging to Mercosur, whose design aims to generate sustainable long-term growth potential by increasing industrialization.…”
Section: Introductionmentioning
confidence: 99%